Problem Solving Learning Model By Integrating ARCS Motivation Strategies On Acid-Base Subjects: Model Pembelajaran Problem Solving Dengan Mengintegrasikan Strategi Motivasi ARCS Pada Materi Pokok Asam Basa - Peni, Natalia; Carvallo, Ludovicus; Priska , Melania (Pedagogia : Jurnal Pendidikan, 2020)
This study aims to produce a chemistry learning model of problem solving by integrating ARCS strategies so that it is feasible to use to improve student learning outcomes in the University of Flores Biology Study Program. The development of the device uses the 4-D model that was tested on semester 2 students of the Biology Education Study Program 2019/2020 Academic Year. The research design used was one group pretest-posttest. Data collection techniques using research instruments, namely in the form of the validity of learning tools, the implementation of the learning plan, student responses, and student learning outcomes. Student learning outcomes data were analyzed using analysis prerequisite tests, which consisted of normality tests, homogeneity tests, and t-tests. The results showed that the device developed was valid. This is evidenced by the significance value of tcount<ttable, which is 0.000<0.05. Thus the developed learning tools can improve student learning outcomes on the subject matter of acid and base.